Organising poetry the Coleridge circle, 1790-1798 - Fairer, David (Oxford University Press, 2009)
Writing their poetry during the 1790s, a decade of European revolution, Coleridge, Wordsworth and their friends have always been thought of as 'the First-Generation Romantics'. This book challenges that concept by viewing them from a new perspective as poets who were continuing an 18th-century 'organic' tradition.